THAILAND SOFT POWER STRATEGY THROUGH BOYS’ LOVE SERIES OF LOVESICK (2014) AND LOVESICK (2024): Strategi Soft Power Thailand melalui Serial Boys Love Lovesick (2014) dan Lovesick (2024) - Abd. Haris Nusa Bela (Universitas Negeri Surabaya, 2025)
The Thailand Boys Love series has become increasingly popular worldwide. Its popularity opens the opportunity for the country to familiarize its cultural values around the world. This research aims to investigate Thailand's attempt to legitimize its soft power agenda through the Boys Love series. Lovesick, the series, serves as a window and object of study for this research to explore these efforts. This study employed a qualitative method with a psychoanalytic visual approach. The data used in this research examined the relationship between images and audience engagement. The finding shows that the Thai government, along with the cultural industry, collaborated to use the Boys Love series to familiarize their soft power. They strengthen it through the visual and remediation of queer gaze presented by two versions of Lovesick the Series. The finding revealed a transformation towards the strategy employed by the Thai government to utilize Boys Love as a tool of soft power legitimation.